Keputusan Pembelian Mahasiswa STIE STEKOM Terhadap Produk Skincare: Peran Kualitas Produk, Harga, dan Promosi dalam Konteks Scarlett Skincare - Lisa Chandra Wardana; Pemilia Pemilia Sulistyowati (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the influence of product quality, price, and promotion on the purchasing decisions of Scarlett Skincare products among students of STIE STEKOM. The local skincare industry is experiencing rapid growth, particularly among young consumers who tend to prioritize high-quality products, affordable prices, and attractive promotional strategies. In this context, understanding the factors that drive purchasing decisions is essential for businesses aiming to remain competitive. A quantitative approach was applied using a survey method, with data collected from 100 purposively selected respondents through structured questionnaires. Multiple linear regression analysis was employed to examine the effects of each independent variable—product quality, price, and promotion—on the dependent variable, namely purchasing decisions. The results indicate that product quality, price, and promotion all have a positive and significant effect—both partially and simultaneously—on purchasing decisions. Among these variables, product quality exerts the most dominant influence compared to price and promotion. This suggests that students are more inclined to purchase skincare products they perceive as effective and safe. These findings contribute theoretically to the study of consumer behavior and marketing management, particularly in the cosmetics sector. Practically, this research provides valuable insights for local beauty product businesses, especially in developing targeted marketing strategies. Emphasis should be placed on maintaining and improving product standards, offering competitive pricing, and enhancing promotional tactics—particularly through digital platforms favored by young consumers. The study recommends improving product innovation and strengthening digital promotion efforts to boost consumer trust, loyalty, and overall purchase intention in a competitive marketplace.